Literasi keuangan dan faktor demografi terhadap perilaku keuangan mahasiswa Fakultas Ekonomi Universitas Negeri Padang - Masdupi, Erni; Sabrina, Syintia; Megawati, Megawati (Jurnal Kajian Manajemen Bisnis, 2019)
The purpose of this research is to analyze (1) financial literacy influences towards behavioral finance (2) the influence of gender against behavioral finance (3) the influence of age against behavioral finance (4) the influence of academic ability against behavioral finance (5) the influence of residence against behavioral finance. The population in this research is the entire S1 students who are actively studies in the Faculty of Economics State University of Padang consist of 1811 people. The samples were selected using clustered proportional sampling to get total samples as much 116 students. The data of this research are primary data and secondary data. The data was analyzed with multiple regression analysis using SPSS version 16,0 program. The results of this research are: (1) financial literacy has a positive and significant relationship on behavioral finance (2) gender has a positive and significant relationship on behavioral finance (3) age has a positive and significant relationship on behavioral finance (4) academic ability has a positive and significant relationship on behavioral finance (5) residence does not have relationship on behavioral financeKeywords: Behaviour finance; financial literacy; demographic factors; academic ability; residence.